2020
DOI: 10.1093/jxb/eraa215
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum induces alterations in the glycerolipidome that confer drought tolerance in wheat

Abstract: Molybdenum (Mo), which is an essential microelement for plant growth, plays important roles in multiple metabolic and physiological processes, including responses to drought and cold stress in wheat. Lipids also have crucial roles in plant adaptions to abiotic stresses. The aim of this study was to use glycerolipidomic and transcriptomic analyses to determine the changes in lipids induced by Mo that are associated with Mo-enhanced drought tolerance in wheat. Mo treatments increased the transcript levels of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 43 publications
3
3
0
Order By: Relevance
“…However, in this study Mo application decreased the contents of MDA, H 2 O 2 and EL in leaves of both rice cultivars (Figure 3), which proves that Mo supplementation alleviates Cd-induced intracellular membrane damages in fragrant rice. These accommodative strategies of Mo to stabilize and sustain bilayer membranes and save cell membranes against oxidative stress damages agree with previous reports in strawberry [47] and wheat [48].…”
Section: Discussionsupporting
confidence: 92%
“…However, in this study Mo application decreased the contents of MDA, H 2 O 2 and EL in leaves of both rice cultivars (Figure 3), which proves that Mo supplementation alleviates Cd-induced intracellular membrane damages in fragrant rice. These accommodative strategies of Mo to stabilize and sustain bilayer membranes and save cell membranes against oxidative stress damages agree with previous reports in strawberry [47] and wheat [48].…”
Section: Discussionsupporting
confidence: 92%
“…Also, molybdenum plays a positive role in preserving the structure and integrity of membranes in wheat leaves, consequently enhancing growth and productivity (Wu et al, 2020). These findings O n l i n e f i r s t align with Al-Ubaidy et al ( 2021) results which demonstrated molybdenum's influence on the electrical conductivity of mung seedlings during drought conditions in the laboratory.…”
Section: Resultssupporting
confidence: 82%
“…Balancing nutrients can enhance the plants tolerance to abiotic stress including cadmium stress by the activation of the enzymatic and non-enzymatic antioxidant defense systems to mitigate the damages caused by the ROS. Many studies proved the vital role of molybdenum in increasing plant tolerance to various abiotic stress (Al-Issawi et al, 2013;Al-Issawi et al, 2016;Wu et al, 2020;. This micronutrient has a very important role in activating the enzymatic and non-enzymatic systems of defense.…”
Section: Introductionmentioning
confidence: 99%
“…Under Brazilian field conditions, the application of Mo via seed or leaves has been shown to be efficient in increasing nodulation, nitrate reductase activity, protein content, leaf area, number of pods, and grain yield ( Calonego et al, 2010 ; Almeida et al, 2013 ; Silva et al, 2017 ; Crusciol et al, 2019 ); however, recent research has demonstrated that Mo also directly impacts photosynthesis due to its involvement in chlorophyll biosynthesis and stability of the photosynthetic apparatus ( Yu et al, 2006 ; Imran et al, 2019 ). In addition, enhancing photosynthesis by adding Mo increases water use efficiency (WUE), leading to greater tolerance of abiotic stresses ( Wu et al, 2020 ). However, these results were obtained in experiments performed under controlled conditions, and the actual effects of Mo supplementation on crop physiology and productivity under field conditions remain unclear.…”
Section: Introductionmentioning
confidence: 99%